Factors influencing construction delays in public investment civil projects: The case of Hanoi, Vietnam - Toan, Nguyen Quoc; Thuy, Nguyen Thi; Linh, Pham Thuy; Huyen, Trinh Khanh; Dung, Pham Thi Ngoc; Lien, Tran Thi Hong; Nhi, Nguyen Yen; Hanh, Nguyen Thi My (Edelweiss Applied Science and Technology, 2025)
Construction delays in public investment civil projects remain a critical challenge in many developing cities, including Hanoi, Vietnam. This study aims to investigate and rank the key factors influencing these delays, providing evidence-based insights for improving project performance. A quantitative research approach was adopted using a structured questionnaire survey targeting 152 construction professionals, including project owners, contractors, consultants, and regulatory authorities. The Relative Importance Index (RII) method was employed to evaluate the significance of seven identified delay factors. The results indicate that contractor capacity (RII = 0.854), supervision consultant capacity (RII = 0.814), and the legal framework for public investment (RII = 0.762) are the most influential contributors to delays. In contrast, socio-economic (RII = 0.720) and natural conditions (RII = 0.700) exert less impact. Based on these findings, the study proposes practical recommendations such as improving contractor evaluation and supervision practices and streamlining legal procedures. The findings have significant implications for policymakers and stakeholders seeking to enhance the effectiveness of public investment in infrastructure, particularly in rapidly urbanizing environments. This research also enriches the global body of knowledge on delay mitigation in public construction projects within emerging economies.